Predictable Changes in Abundance, Composition, and Size Structure of Fish and Macroinvertebrates Along an Urbanization Gradient in the Ottawa-Gatineau Area - Duhaime, Johannie (Université d'Ottawa / University of Ottawa, 2012)
As land use transformations are the main driver of biological diversity loss at the global scale, it is essential to provide predictions and understanding of their impacts in order to improve the mitigation of ecosystem perturbations. The first objective of this project was to describe the response of biological assemblages along a gradient of urbanization and to compare metrics of watershed imperviousness in order to determine, as has been suggested in the literature, whether effective imperviousness, which represents the proportion of impervious area directly connected to the stream by storm sewers, is a better predictor of stream impairement than total imperviousness in the watershed. Decline in sensitive taxa abundance is initiated at 14% total imperviousness and 3% effective imperviousness in the Ottawa-Carleton region and, total and effective imperviousness have equivalent predictive power. The second objective of this project was to describe how the structure of metazoan assemblages in urban streams, as described by size spectra attributes (i.e. slopes, intercepts, number of logarithmic size classes occupied, and residual variance), varies with watershed size, land use and water quality. Streams size spectra of the Ottawa-Gatineau region have relatively shallow slopes, reflecting relatively higher densities of organisms in the larger size classes compared to other ecosystem types (e.g. lakes, oceans, soils, coastal waters). Size spectra slopes, density corrected for size, number of size classes, and residual variance vary predictably along gradients of watershed size, watershed proportion of natural land use and periphyton chlorophyll a. A systematic trend of declining spectra slopes with increasing periphyton biomass suggests that ecological efficiency declines in urban eutrophic streams.
Keywords: Total imperviousness; Effective imperviousness; Urbanization; Land use changes; Macroinvertebrates; Fish; Periphyton chlorophyll a; Water Quality; Size spectra; Threshold